Forensic and Legal Dentistry - Rötzscher, Klaus (Springer International Publishing : Imprint: Springer, 2014)
There is an increasing need for legal knowledge in the relationship between dentist and patient, as more and more often the dentist and the patient are meeting again in court. It is therefore advisable for the dentist to be familiar with the basics of law as it relates to dentistry, and especially the law of tort (including negligence and breach of duty of care). In addition, of course, dentists may be called upon to give evidence as impartial experts in legal cases. This book both explains in detail diverse aspects of the law relating to dentistry and examines key issues in forensic odontostomatology. A central aim is to enable the dentist to achieve a realistic assessment of the legal situation and to reduce uncertainties and liability risk. To this end, experts from across the world discuss the dental law in their own countries, covering both civil and criminal law and highlighting key aspects such as patient rights, insurance, and compensation. In the section on forensic odontostomatology, extensive guidance is provided on development of the dentition, clinical findings and documentation, personal identification, age estimation, and the nature and significance of bite, tooth, and lip marks. This book will be an interesting and helpful source of information for all who practice in the field of dentistry as well as forensic scientists, lawyers, investigative and identification authorities, criminologists, prosecutors, insurance agents, and students.